The Effectiveness of Caudal Block with Low Doses of Dexmedetomidine and Pethidine in Transrectal Prostate Biopsy: Preliminary Results - ÇAM, HAYDAR KAMİL (TAYLOR & FRANCIS INC, 2022)
Purpose To evaluate the effectiveness of caudal block (CB) using dexmedetomidine and pethidine instead of local anesthesia (LA) for prostate needle biopsy and the effect of CB on urinary retention. Material and Methods A transrectal ultrasound-guided prostate needle biopsy (TRUS-Bx) was performed on 68 patients with a mean age of 65 +/- 2.18 years. CB with a combination of dexmedetomidine and pethidine without LA was administered to the patients. The pain levels of the patients were determined using numeric rating scale (NRS) scores to evaluate the effectiveness of CB. Preoperative and postoperative postvoid residual urine volumes (PRUV) were also calculated. Results The CB success rate was 93.15%. The NRS scores were 0.79 +/- 0.19 and 0.89 +/- 0.22 during probe entry and manipulation and biopsy, respectively, without any significant differences between them (p = 0.382). The mean PRUVs before and after biopsy did not differ significantly (41 +/- 15.6 vs. 71.93 +/- 22.3, p = 0.379). The degree of sedation, as assessed using the Ramsay scale, was 2 or 3 in all patients. Conclusion The combination of dexmedetomidine and pethidine for CB in TRUS-Bx provided quality analgesia for the patient and prevented the development of postoperative urinary retention.
Keywords: Anesthesia; complication; dexmedetomidine; pethidine; prostate biopsy; urinary retention